MENDUKUNG KEPATUHAN PENGOBATAN DENGAN BERBAGI KEBAHAGIAAN DAN MENJADI SAHABAT: STUDI KASUS DI KOMUNITAS SAHABAT ANAK KANKER MALANG, INDONESIA - Febriana Ira Handian; Yeni Fitria; Mahmudatul Rodliyatil Falah (Universitas Muhammadiyah Jember, 2017)
Treatment compliance of Acute Lymphoblastic Leukemia (ALL) important toimprove morbidity and one of keys to successful treatment in children with ALL. Sahabat Anak Kanker Malang is a non-state community of self help group cancer engaged to build positive perceptions of patients and families about the fight against cancer in Indonesia. By elaborating Friedmans role theory as a theoretical framework, this research is aimed to explore the role concept self help group cancer childhood to support compliance care of parent in ALL children. Moreover, this study also contribute to introducing self help group cancer role framework to the community and health workers as an alternative compliance improvement programs based on community and give alternative program for other cancer communites in Indonesia in determining support programs for ALL. This study was conducted by case study in qualitative design with 25 participants from volunteers, health workers and the community. Data conducted in Komunitas Sahabat Anak Kanker Malang, Malang City of East Java and Surroundings Area by participatory observation, in-depth interview and focus group discussion. Data were analyzed with data reduction, display, conclusion, verification and assisted by opencode software 4.0. This research found that this community offered a major program to share happiness with cancer children and being friends for them, motivators as well as facilitators for medication compliance, develop fun hospital atmosphere for children and gain networking to support patients and parents. Although they faces difficulties when interacting with health worker technically in the treatment room, the activities undertaken by this community get wide positive responses as an alternative program and complete maintenance activities that can not be fully done by the hospitalKeywords: Treatment Compliance, Self Help Group, Cancer, Acute Lymphoblastic Leukemia, Non-State Community